The works of Arthur Murphy, esq. ... : in seven volumes. - Murphy, Arthur, 1727-1805. (Tufts University. Tisch Library., 2015)
Volume 2 of 7.; 1 online resource (7 volumes); Electronic reproduction. Medford, MA : Tisch Library, Tufts University, 2015. Scanned by the Boston Library Consortium/Open Content Alliance as part of the BLC OCA Digitization Project from a copy at the Tisch Library, Tufts University.; Indexed in: English short title catalogueT147516